Investigation of Cure Reaction, Rheology, Volume Shrinkage and Thermomechanical Properties of Nano-TiO2 Filled Epoxy/DDS Composites. (5th August 2013) - Parameswaranpillai, Jyotishkumar; George, Abhilash; Pionteck, Jürgen; Thomas, Sabu
Abstract : The cure reaction, rheology, volume shrinkage, and thermomechanical behavior of epoxy-TiO2 nanocomposites based on diglycidyl ether of bisphenol A cured with 4, 4′-diaminodiphenylsulfone have been investigated. The FTIR results show that, at the initial curing stage, TiO2 acts as a catalyst and facilitates the curing. The catalytic effect of TiO2 was further confirmed by the decrease in maximum exothermal peak temperature (DSC results); however, it was also found that the addition of TiO2 decreases the overall degree of cure, as evidenced by lower total heat of reaction of the cured composites compared to neat epoxy. The importance of cure rheology in the microstructure formation during curing was explored by using rheometry. From the PVT studies, it was found that TiO2 decreases the volume shrinkage behavior of the epoxy matrix. The mechanical properties of the cured epoxy composites, such as tensile strength, tensile modulus, flexural strength, flexural modulus, impact strength, and fracture toughness of the polymer composites, were examined. The nanocomposites exhibited good improvement in dimensional, thermal, and mechanical properties with respect to neat cross-linked epoxy system. FESEM micrographs of fractured surfaces were examined to understand the toughening mechanism.